PENEGAKAN HUKUM PIDANATERHADAP KORBAN PECANDU NARKOBA DI INDONESIA - Rustandi Senjaya (JOURNAL OF LAW AND NATION, 2022)
The government's criminal policy on the issuance of the drug-related law no. 35 of 2009 especially for drug addicts needs to be implemented according to the constitutional mandate. That the government has an obligation to protect the homeland and its citizens from any form of threat. Including the threat of the dangers of drugs, which are consciously and deliberately spread among the community, especially the younger generation as the nation's successor. Currently, drug users are suspected of reaching 5.1 million, or even more. Because the number of drug users is like an iceberg (ice berg) and experiencing dark numbers (dark numbers). It is hoped that the criminal policy of the issuance of this law will be able to overcome or at least reduce the number of drug users, one of which is creating new breakthroughs by decriminalizing drug users without having to get prison sanctions. As mentioned that the guarantee of legal protection given to narcotics addicts is regulated by Law no. 35 of 2009 concerning Narcotics by providing both medical and social rehabilitation as stated in Article 54 of the Narcotics Law. Namely that "narcotics addicts and addicts of narcotics abuse are obliged to undergo medical rehabilitation and social rehabilitation".